Pengaruh Variasi Lip Thickness Pada Nozzle Terpancung Dengan Swirl Terhadap Kestabilan Api Difusi Concentric Jet Flow - Kris Witono; Akhsanu Takwim (Jurnal Energi dan Teknologi Manufaktur, 2018)
One of the factors that affect flame diffusion characteristics is the geometry of fuel nozzles in the installation of the combustion system. The nozzle shape greatly affects the turbulence that occurs between fuel and air. This process causes the formation of flow recirculation zones. This process thus produces homogeneous mixing and obtains near perfect combustion. The recirculation zones are zones arising from breaking the flow rate. So as to cause a vortex and backflow around the tip of the nozzle. It is this feedback which inhibits and simultaneously suppresses the flame so that the flow rate of the fuel mixture and the air is maintained lower or equal to the flame velocity. In this study, lip thickness variations in nozzles were used with swirls with variations of 0, 4, 8, 12, and 16 mm to determine flame stability of concentric jet flow diffusion. Fuel velocity and air are varied to obtain flame stability data. In addition, to support and reinforce the results obtained from this study, direct photograph and shadowgraph methods are used to obtain flow pattern visualization. The result of the research shows that the stability of flame concentric jet flow diffusion has increased along with the decreasing of lip thickness in nozzle. The largest flame stability area is obtained in 4 mm thick lip thickness.